Disentangling the functioning of native soil microbes in enhancing nutritional value of Aloe vera and soil health parameters - Chandel, Neha Singh; Singh, H. B.; Vaishnav, Anukool (Frontiers in Soil Science, 2025)
Soil salinity is a significant global issue that adversely affects plant growth by reducing the availability of essential nutrients, leading to deficiencies. This presents challenges for the production of medicinal plants, as their value relies on nutrient-dependent metabolites. To address this, bioremediation strategies using living organisms have gained attention. Native bacteria in saline soils offer a sustainable way to restore soil health and mitigate salt stress. This study investigates the impact of native rhizosphere soil bacteria on the growth and nutritional value of Aloe vera. We screened four bacterial isolates from the rhizosphere of A. vera plants grown in saline soil in the Mathura region of Uttar Pradesh, India, focusing on their nutrient-solubilizing abilities. These bacterial strains demonstrated phosphate solubilization, potassium solubilization, siderophore production, indole-3-acetic acid (IAA) production, and protease activity. Using partial 16S rRNA gene sequencing, bacterial isolates were identified as Paenibacillus sp., Arthrobacter sp., Pseudomonas sp., and Bacillus sp. Subsequently, a pot experiment was conducted to augment the population of these bacteria in the soil and to evaluate their impact on A. vera’s growth and nutritional value. The bacteria were applied both individually and as a consortium. To assess the impact of these inoculations, the nutrient content of leaf gel and various soil health parameters were measured. The results showed that the application of the bacterial consortium yielded higher number of leaves (47%), leaf fresh weight (74%), gel content (33%), and nutritional properties as compared to control treatment (non-inoculated). Furthermore, bacterial inoculation significantly enhanced soil enzymatic activity and increased the soluble nitrate and phosphate content in the experimental soil. In conclusion, the presence of these bacteria in the rhizosphere of A. vera, along with their nutrient-solubilizing activities, enhances nutrient uptake and metabolite synthesis in the host plant under saline soil conditions.